2012
DOI: 10.1063/1.3662959
|View full text |Cite
|
Sign up to set email alerts
|

Initial study of the optical spectrum of the ISIS H− ion source plasma

Abstract: The front end test stand is being constructed at the Rutherford Appleton Laboratory, with the aim of producing a 60 mA, 2 ms, 50 Hz, perfectly chopped H(-) ion beam. To meet the beam requirements, a more detailed understanding of the ion source plasma is required. To this end, an initial study is made of the optical spectrum of the plasma using a digital spectrometer. The atomic and molecular emission lines of hydrogen and caesium are clearly distinguished and a quantitative comparison is made when the ion sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is possible to work out the electron temperature k B T e from the ratios of the peaks. 3 The electron temperature does not increase for discharge currents greater than 80 A as shown in Fig. 6.…”
Section: B Vary Pulsed Discharge Currentmentioning
confidence: 83%
“…It is possible to work out the electron temperature k B T e from the ratios of the peaks. 3 The electron temperature does not increase for discharge currents greater than 80 A as shown in Fig. 6.…”
Section: B Vary Pulsed Discharge Currentmentioning
confidence: 83%
“…Some research indicated that the electron temperature can be determined using the line intensity ratio of hydrogen. [21,22] This method is also used in our work by measuring the line intensities of H α and H β for the determination of the electron temperature. Figure 15 presents the results for pure hydrogen and hydrogen with noble gas (gas mixture).…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Fig. 5 shows the improvement in quality of data to be expected with the new monochromator, compared with the Stellarnet CCD spectrometer used in an initial plasma spectroscopy study [12]. Lessons Learnt to be Implemented in the VESPA Mk.…”
Section: Emission Spectroscopymentioning
confidence: 99%